In vitro phytochemical and antimicrobial screening of Thymus linearis - Naz, Attiqa; Saeed, Muhammad; Hussain, Muhammad Medrar; Ishaq, Muhammad Saqib (Bangladesh Journal of Pharmacology, 2015)
Extracts from the whole plant of Thymus linearis were extracted with methanol (crude), chloroform, n-hexane, ethyl acetate and butanol and screened for their phytochemical and antimicrobial potentials. Preliminary phytochemical screening of plant extracts manifests the existence of terpenoids, flavonoids, tannins, alkaloids, glycosides and reducing sugars. Fourier transform infrared spectroscopy studies were carried out on various phytochemicals extracted from the extracts of T. linearis which results in the presence of different compounds like amides, aldehydes, carboxylic acid, ethers, alcohol and ketones. All the extracts of T. linearis showed significant antibacterial and antifungal activities when tested against nine bacterial and four fungal strains. It was concluded from this study that extracts of T. linearis have an array of important phytochemicals and significant activities against some of the multidrug resistant bacterial and medically important fungal strains.